(Invited) Electrodeposited Micro Thermoelectric Module Design for Hybrid Semiconductor Laser Cooling on a Silicon Photonics Platform. (14th September 2015) - Enright, Ryan; Lei, Shenghui; Mathews, Ian; Cunningham, Graeme; Frizzell, Ronan; Shen, Alexandre
Abstract : Integrated silicon photonics has emerged as a scalable solution to meet the demands for increased bandwidth in communication networks. However, integration introduces new thermal challenges for active photonic device performance. Traditionally, temperature sensitive devices have been isolated and cooled using centimeter-scale thermoelectric modules. An alternative approach is to integrate thermoelectric temperature control at the device level that simultaneously provides targeted cooling for individual temperature sensitive devices and reduces the footprint of the thermal solution to enable full optoelectronic integration. Here we present the design of a micro thermoelectric cooler based on electrodeposited bismuth telluride integrated around a hybrid laser. We briefly outline the thermal requirements to ensure good hybrid laser performance. We then develop a multiphysics numerical model of the hybrid laser with integrated μTEC and assess our design in terms of system-level relevant operating temperatures. Our results suggest that electrodeposited μTECs can meet the thermal requirements of active photonics devices in silicon photonics under realistic operating conditions.